THE IMPLEMENTATION OF INTERACTIVE MULTIMEDIA IN IMPROVING MATHEMATICS LEARNING OUTCOMES - Nurmawati Nurmawati; Lusi Rachmiazasi Masduki; Edy Prayitno; Maria Yustina Rensi Dartani (Universitas PGRI Semarang, 2020)
Mathematics is a difficult subject and even becomes a phobia, more due to teaching conventionally in where the teaching and learning process emphasizes more on teacher, working on problems, memorization and speed of arithmetic, so students lack understanding of what they are learning, which in this case does not have an understanding of the concepts taught. Students tends to be lazy and have low motivation to study mathematics both classically and to study independently at home. The growth of information and communication technology in society is reflected in policies to encourage the use of ICT in education and the development of educational multimedia. Multimedia includes using text, images, animation, video and audio to prepare courses for students in various levels of education. Attendance of multimedia technology can help students learn to be more interesting and help students understanding in learning. The purpose of the study was to know whether there was any significant difference in the result between the students of class IV Manyaran 01 Elementary School towards increasing their understanding in math who taught by using the interactive multimedia and who taught by conventionally. The result of the study showed that the interactive multimedia gave an effect to the improvement of the students’ understanding in mathematics.